Community Pharmacist and Clinical Pharmacist Interventions using MMAS-8, FACIT, SF-12 among Pulmonary TB Patients Receiving Anti-TB Drugs from Urban Community Pharmacies, South India - Rangaswamy, Uday Kumar; Ganachari, Madiwalayya Shivakantayya (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim and Objectives: To determine the professional interaction between community pharmacist and clinical pharmacist during the treatment of pulmonary tuberculosis (TB) patients at urban community pharmacy. Methods: A randomized controlled study was conducted in the urban area of Belagavi city, India. Community pharmacist and clinical pharmacist intervention using Developed KAP (Knowledge, Attitude and practice) questionnaires, Morisky Medication Adherence Scale (MMAS-8), FACIT- Satisfaction with Pharmacist Scale, Health-related QoL (SF-12). Results: A total of 350 community pharmacies were surveyed for this study. Total of 87 (37.7%) community pharmacies had a working dispensable stock of anti-TB medicines first-line. Majority of patients 29 (58 %) from the urban area. Adherence behavior was changed from 2% to 92% (at follow-up visit 3). Patient Statistical significance (*p<0.05) towards clinical and community pharmacists by patients. All health-related components of QoL SF-12 were significantly improved at six months, except for the energy and fatigue (VT) portion. Conclusion: We noticed that the community pharmacists who took part in our research demonstrated a clear tendency to cooperate with clinical pharmacist, but that disposition has not yet been reciprocal. Community pharmacists must also become acquainted with professional interactions in the health system of (TB) during their educational classes, during their continuing education in pharmacy and after graduation and try to eliminate the existing imperfections.
Keywords: Community Pharmacists; Clinical Pharmacists; Pulmonary Tuberculosis; Quality of life; Medication Adherence; Knowledge; Attitude and Practice (KAP)